An introduction to English phonology - McMahon, April (b, 2020)
This textbook introduces the main units and concepts you require to describe speech sounds accurately. By working through the book and the various exercises included, you will come to understand the need for a dedicated system of description and transcription for speech sounds, and for a degree of phonological abstraction to support our understanding of the behaviour of sounds in particular languages and varieties. You will learn to carry out elementary, broad phonetic transcription, and be able to establish contrastive vowel and consonant systems for your own varieties and to express simple generalisations reflecting the productive and predictable patterns of English sounds. At the end of the book there is a section guiding you through some of the exercises and there is also a detailed glossary which will be useful for assignments or revision during exams.
Includes bibliographical references and index.
Keywords: English language -- Phonology; Languages; Language